Bacterial diversity in persistent periapical lesions on root-filled teeth - Handal, Trude (CoAction Publishing, 2009)
BACKGROUND: The purpose of this study was to analyze the bacterial diversity in persistent apical lesions on root-filled teeth by using culture-independent molecular methods. DESIGN: Twenty surgically removed apical lesions from therapy-resistant teeth were examined for the presence of bacterial DNA using PCR targeting the 16s ribosomal RNA gene, followed by cloning and sequencing. RESULTS: Bacterial DNA was detected in 17 of the 20 samples (85%). A total of 236 clones were analyzed. Seven different bacterial phyla were represented and a total of 75 different bacterial taxa were identified; 36% of the species have not yet been cultivated. Commonly detected bacterial species included Fusobacterium spp., Prevotella spp., Tannerella forsythia, Porphyromonas endodontalis, Treponema denticola, Bacteroidetes spp., Peptostreptococcus spp., and Streptococcus spp. CONCLUSIONS: A wide range of bacteria was identified in periapical lesions on therapy-resistant teeth. These bacteria may contribute in the etiology of periapical infection and impede healing of these lesions.